Validasi Jarak pada Pneumatic Tube System terhadap Hasil Pemeriksaan Trombosit (PLT) dan Kalium - Yoki Setyaji; Tri Novitasari; Inggil Tunjung Muktianafi; Shintia Dini Anggreini; Norma Agustin Palupi (Poltekkes Kemenkes Semarang, 2022)
Pneumatic tube system (PTS) is a sample transport medium that is widely used in hospitals. Samples sent using PTS may be shaken due to the varying speed and air pressure in the PTS. The use of PTS can affect the examination of platelet counts and potassium levels. The installation of PTS at the Gadjah Mada University Academic Hospital was carried out in May 2020 in the Yudistira, Arjuna, Kresna and Nakula buildings. Delivery of laboratory samples at RSA UGM every day can be done from buildings with different distances. Every hospital that uses PTS is advised to validate PTS and investigate blood specimens for the possibility of hemolysis and laboratory results. The purpose of this study was to validate the PTS distance as a transport medium for laboratory examinations. This research is an experimental research which is a follow-up study using 30 samples. Samples were taken twice and sent with the PTS from two different distances, namely YD 2 and IGD. The statistical test will use a paired sample t-test. The data will be analyzed with the help of Prima Graph 8 Statistical Software with a significance level of 5%. The results of the analysis showed that there was no difference in the results of the examination of platelets and potassium sent from YD 2 or from the ER.